Pursuing underlying values: A community value-based approach to ‘Hijau Manise’ greening program in East Sumba, East Nusa Tenggara - Nurfitria Ramadhani Astrid; Iman Nurul (BIO Web of Conferences)
Since 2019, East Sumba has faced extreme drought, exacerbating poverty and food insecurity. Greening initiatives, by fostering microclimate regulation, offer a potential solution to induce rainfall and improve soil fertility, thereby supporting sustainable agriculture. Despite various past greening initiatives, many have failed due to technical challenges (low rainfall, high evaporation rates, and rocky terrain) and social barriers (lack of community attachment to the planted trees due to delayed benefits).To address these challenges, this study adopts a Participatory Action Research (PAR) approach across seven villages in five sub-districts of East Sumba. The research specifically examines how Hijau Manise, a CSR initiative by PT Muria Sumba Manis, integrates a community value-based approach in its planning and implementation. A qualitative approach, incorporating in-depth interviews, FGDs, and observations, was used to analyze emerging values that influence community engagement with the planted trees. To ensure validity and reliability, findings were triangulated across multiple data sources, validated with stakeholders, and refined through iterative reflection cycles. Findings reveal that prosperity and social justice are the most influential values in fostering long-term community commitment, while liberty and sustainability serve as supporting enablers. The study underscores the importance of continuous stakeholder involvement at every stage—from planning to evaluation—to ensure sustainable and community-driven greening efforts.